2018
DOI: 10.1155/2018/2657461
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Modelling of Bacterial Meningitis Transmission Dynamics with Control Measures

Abstract: Vaccination and treatment are the most effective ways of controlling the transmission of most infectious diseases. While vaccination helps susceptible individuals to build either a long-term immunity or short-term immunity, treatment reduces the number of disease-induced deaths and the number of infectious individuals in a community/nation. In this paper, a nonlinear deterministic model with time-dependent controls has been proposed to describe the dynamics of bacterial meningitis in a population. The model is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 43 publications
0
25
0
3
Order By: Relevance
“…Hampir semua bakteri yang masuk ke meninges dapat menyebabkan meningitis. Meningitis bakteri umumnya disebabkan oleh tiga bakteri yaitu Neisseria meningitidis, Haemophilus influenzae, dan Streptococcus pneumoniae [6]. Meningitis bakteri hanya ditemukan pada manusia dan ditularkan dari satu orang ke orang lain [7].…”
Section: Pendahuluanunclassified
“…Hampir semua bakteri yang masuk ke meninges dapat menyebabkan meningitis. Meningitis bakteri umumnya disebabkan oleh tiga bakteri yaitu Neisseria meningitidis, Haemophilus influenzae, dan Streptococcus pneumoniae [6]. Meningitis bakteri hanya ditemukan pada manusia dan ditularkan dari satu orang ke orang lain [7].…”
Section: Pendahuluanunclassified
“…dt from (2) into (8) and collecting all positive terms together and also negative terms together, we obtain…”
Section: Global Stability Of Eementioning
confidence: 99%
“…Several scholars have developed different models to study the dynamics of different epidemic diseases. Some of them [7,8] proposed a mathematical model of pneumonia and meningitis; moreover, [9] investigated the co-dynamics of pneumonia and typhoid fever diseases with optimal control and cost-effectiveness analysis. The result of the study revealed that prevention of typhoid fever and treatment of pneumonia is the most cost-effective strategies from the proposed ones.…”
Section: Introductionmentioning
confidence: 99%
“…Meningitis vaccine contains antigens, a substance that stimulates the immune system to form antibodies and fight the bacteria that cause meningitis, hence vaccine can reduce the risk of meningococcal Meningitis disease. Mathematics research about meningitis vaccine using control had done by Asamoah, et al (2018). Blyuss (2016) also had discussed temporary population immunity to meningitis disease which can be useful to measure the efficiency of vaccines.…”
Section: Introductionmentioning
confidence: 99%
“…The incubation period of meningococcal disease is 3 to 4 days, with a range of 2 to 10 days. Meningitis is the most common presentation of invasive meningococcal infection (meningococcal disease) and results from hematogenous dissemination of the organism (Asamoah, et al 2018). So, time unit (t) is assumed to be calculated in weeks because the incubation period may exceed seven days (one week).…”
Section: Introductionmentioning
confidence: 99%